2022
DOI: 10.26508/lsa.202201627
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activation of RARβ and RARγ nuclear receptors restores cell specialization during stem cell differentiation by hijacking RARα-controlled programs

Abstract: How cells respond to different external cues to develop along defined cell lineages to form complex tissues is a major question in systems biology. Here, we investigated the potential of retinoic acid receptor (RAR)–selective synthetic agonists to activate the gene regulatory programs driving cell specialization during nervous tissue formation from embryonic carcinoma (P19) and mouse embryonic (E14) stem cells. Specifically, we found that the synergistic activation of the RARβ and RARγ by selective ligands (BM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In contrast, RARβ and RARγ coactivation in either RARβ (−/−) or RARγ (−/−) cells presented a poor yield of upregulated genes associated with the studied neuronal subtypes or glial cells (Figure 2B), in agreement with the low cell differentiation performance. Finally, it is worth mentioning that these findings performed in P19 embryonal carcinoma cells were also confirmed in mouse embryonic stem cells, confirming the potency of the synergistic action of both RARβ and RARγ agonists to lead to neuronal cell specialization (Figure 2C) [25].…”
Section: In Vitro Studies Modeling Neuronal Cell Specializationsupporting
confidence: 70%
See 4 more Smart Citations
“…In contrast, RARβ and RARγ coactivation in either RARβ (−/−) or RARγ (−/−) cells presented a poor yield of upregulated genes associated with the studied neuronal subtypes or glial cells (Figure 2B), in agreement with the low cell differentiation performance. Finally, it is worth mentioning that these findings performed in P19 embryonal carcinoma cells were also confirmed in mouse embryonic stem cells, confirming the potency of the synergistic action of both RARβ and RARγ agonists to lead to neuronal cell specialization (Figure 2C) [25].…”
Section: In Vitro Studies Modeling Neuronal Cell Specializationsupporting
confidence: 70%
“…More recently, we found that, while RARβ or RARγ agonists are not able to induce neurogenesis, their synergistic action surprisingly allows them to do so, demonstrating that there exist redundant pathways driven by each RAR subtype, but also their distinctive influence [25]. In this study, in addition to the use of synthetic RAR agonists, we generated P19 CRISPR-Cas9 RAR knock-out lines, providing means to evaluate the redundancy between RARs (Figure 2A).…”
Section: In Vitro Studies Modeling Neuronal Cell Specializationmentioning
confidence: 80%
See 3 more Smart Citations